The Influence of the Chemical Composition and Temperature of Molten Rocks on Laws Wetting Their Platinum-Rhodium Plate Spinneret - Diduk, I.I.; Bagliuk, G.A. (Physics and Chemistry of Solid State, 2015)
The results of investigation of platinum-rhodium substrate wetting by the melts of ten different compositions of rocks and the values ​​of their surface tension and adhesion in a wide temperature range. It is shown that the highest values ​​of surface tension and adhesion observed for basalt melts, whereas neutral aluminosilicate glass melts, which do not containiron oxide compounds are characterized by a high value of the contact angle and the lowest values ​​of surface forces. Doping of ZrO2in the meltcompositionsignificantly increases angles of wetting and surface tension and adhesion throughout the temperature range as compared with the same melts without zirconia.